A novel SDS-stable dimer of a heterogeneous nuclear ribonucleoprotein at presynaptic terminals of squid neurons. (6th August 2015) - Lico, D.T.P.; Lopes, G.S.; Brusco, J.; Rosa, J.C.; Gould, R.M.; De Giorgis, J.A.; Larson, R.E.
Highlights: We identified a novel SDS-stable dimer of hnRNPA/B-like protein in squid pre-synaptic terminals. Mono- and dimeric hnRNPA/B-like proteins were differentially associated with cellular components. hnRNPA/B-like protein localized with synaptic vesicle protein Sv2 and RNA-binding protein ELAV. Data mining into squid databases illustrated the complexity of the hnRNPA/B subfamily. Analysis of the stability of the hnRNPA/B-like dimer may give clues to misfolding in disease states. Abstract: The presence of mRNAs in synaptic terminals and their regulated translation are important factors in neuronal communication and plasticity. Heterogeneous nuclear ribonucleoprotein (hnRNP) complexes are involved in the translocation, stability, and subcellular localization of mRNA and the regulation of its translation. Defects in these processes and mutations in components of the hnRNP complexes have been related to the formation of cytoplasmic inclusion bodies and neurodegenerative diseases. Despite much data on mRNA localization and evidence for protein synthesis, as well as the presence of translation machinery, in axons and presynaptic terminals, the identity of RNA-binding proteins involved in RNA transport and function in presynaptic regions is lacking. We previously characterized a strongly basic RNA-binding protein (p65), member of the hnRNPA/B subfamily, in squid presynaptic terminals. Intriguingly, in sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE), p65 migrated as a 65-kDa protein, whereas members of the hnRNPA/B family typically have molecular masses ranging from 35 to 42 kDa. In this report we present further biochemical and molecular characterization that shows endogenous p65 to be an SDS-stable dimer composed of ∼37-kDa hnRNPA/B-like subunits. We cloned and expressed a recombinant protein corresponding to squid hnRNPA/B-like protein and showed its propensity to aggregate and form SDS-stable dimers in vitro . Our data suggest that this unique hnRNPA/B-like protein co-localizes with synaptic vesicle protein 2 and RNA-binding protein ELAV and thus may serve as a link between local mRNA processing and presynaptic function and regulation.